In Vitro Evaluation of the Antibacterial Activity of Zingiber officinale (Ginger) Against Salmonella Typhi - Rahman, Md. Abdur; Nipu, Shaon Akter; Nahar, Dewan Nilima; Dip, Rashidul Islam; Mamun, Shamsul Huda; Mostofa, Fatima Binte; Bashir, Md Samiul; Rahman, Md. Ashiqur (Bangladesh Journal of Infectious Diseases, 2026)
Background: Antimicrobial resistance in Salmonella Typhi poses a significant public health challenge, particularly in developing countries like Bangladesh. Plant-based therapies are potential alternative antimicrobial agents due to their bioactive compounds. Objective: This study was aimed to evaluate the in vitro antibacterial activity of crude ginger extract (CGE) and ethanolic ginger extract (EGE) against Salmonella Typhi and compare their efficacy with the standard antibiotic Amikacin. Methodology: This experimental study was conducted at the Department of Pharmacology and Therapeutics in collaboration with the Department of Microbiology, Mymensingh Medical College, Bangladesh, from July 2016 to June 2017. Crude and ethanolic extracts of ginger were prepared from fresh rhizomes. Antibacterial activity was assessed using nutrient agar incorporation for crude ginger extract (CGE) and disc diffusion assays for ethanolic ginger extract (EGE). Minimum inhibitory concentrations (MICs) were determined using broth dilution techniques. Results: CGE inhibited Salmonella Typhi growth at concentrations ≥50%, with complete inhibition at 100% concentration. EGE showed strong, dose-dependent antibacterial activity, with inhibition zones measuring 14 mm, 30 mm, and 33 mm at 25, 50, and 100 µg/10 µl, respectively. The MIC of EGE was 500 µg/ml, while Amikacin exhibited a significantly lower MIC of 1.5 µg/ml, confirming its higher potency. Subculture studies demonstrated bactericidal effects for CGE at 100%, EGE at 500 µg/ml, and Amikacin at 1.5 µg/ml. The study highlights that EGE was more effective than CGE, but less potent than the standard antibiotic, supporting its potential use as a complementary antimicrobial agent. Conclusion: Both crude and ethanolic ginger extracts demonstrated antibacterial activity against Salmonella Typhi, with ethanolic extract showing stronger, dose-dependent effects. While Amikacin was more potent, ginger extracts may serve as potential natural antimicrobial agents. Bangladesh Journal of Infectious Diseases, December 2025;12(2):260-266